Development of fishing vessel shipyard in traditional Lampulo, Banda Aceh. Issue 1 (November 2021) - Rizwan, T; Muhammad, M; Arif, M; Agustina, I; Rahayu, R
Abstract: The construction of ships at the Lampulo shipyard has not all used the rules according to naval architecture. But there may be ineffectiveness in the use of raw materials such as a lot of wasted wood volume. This research was conducted to know the types of wood and equipment used for traditional shipbuilding and know the process of traditional shipbuilding. This research used a survey method and data was collected by interviewing and observation. This research is located in the Kutaraja Ocean Fishery Port, Banda Aceh conducted from March to April 2021. The results showed that the types of wood commonly used as raw materials for shipbuilding in traditional shipyards were bangkirai wood ( Shore Laevifolia Endert), laban wood (Vitex Punesceus Vahl), balau wood ( Hopea Calebica Burck ), meranti merah wood (Shorea Acuminata Dyer ), tembusu wood ( Fagraea Fragrans Roxb ), bungur wood (Lagerstroemia Speciosa Pers), and merbau wood (Intsia Bijuga) . The equipment used still uses non-electronic equipment, only drill work that uses electricity. Meanwhile, the traditional shipbuilding process generally begins with laying the keel and installing the crest. Next, continued by frames installation, hull plank then upper hull main frame. Hereinafter, deck floor installation, hatches manufacture, and superstructure construction. The final stage of shipbuilding process is machining, painting, installing engines, propellers, and steering. Thus it can be said that the construction of a fishing vessel in Lampulo still traditionally a hereditary habits.